DESIGN FIBER TO THE HOME GIGABIT PASSIVE OPTICAL NETWORK UDAYANA UNIVERSITY, SUDIRMAN CAMPUS - Sudiarta, Pande Ketut; Alit Swamardika, Ida Bagus; Gunantara, Nyoman (Journal of Electrical, Electronics and Informatics, 2021)
To find out the need for fiber optic access network devices from NOC to rooms at Udayana University, Sudirman Campus, fiber to the home network design was made with Gigabit Passive Optical Network (GPON) technology. Selection of GPON technology to reduce the number of ports on OLT and the number of fiber cores compared to the existing technology using point to point. Assuming the bitrate in each room is 21 Mbps and 291 rooms to be served, it takes 5 OLT ports on the NOC. Feeder Cable Network consists of 5 cores distributed to each location using 3 units of 1: 4 splitter, 4 units of 1: 8 splitter, 6 units of 1:16 splitter, 1:32 splitter of 6 units. To maintain service quality, 16 amplifiers are needed. The required fiber cable length is 2.5 km. The quality of service is tested using the Optisystem simulator. The result is that at the closest distance the PRx value is -14.059 dBm, with BER 6.13608 e-103, Q Factor 21.511. Meanwhile, at the farthest distance, the PRx value is -14.105 dBm, with BER of 1.52751 e-120, and Q Factor 23.3159. The results obtained still meet the ITU-T G.984.2 standard